2011
DOI: 10.2298/sos1101021e
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of mill scale in sintering process

Abstract: This investigation deals with the effect of replacing some amount of Baharia high barite iron ore concentrate by mill scale waste which was characterized by high iron oxide content on the parameters of the sintering process., and investigation the effect of different amount of coke breeze added on sintering process parameters when using 5% mill scale waste with 95% iron ore concentrate. The results of this work show that, replacement of iron ore concentrate with mill scale increases the amount of ready m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 4 publications
0
26
0
3
Order By: Relevance
“…However, mill scale containing oil must pass through treatment to remove this contaminant Bagatini et al (2011);El-Hussiny et al (2011);Martín et al (2012); Umadevi et al (2012) Manufacture of pigments It is possible to prepare various pigment shades based on iron oxide through a simple method (based on precipitation and calcination) and low cost Legodi and Dewaal (2007) Management routes of galvanic sludge.…”
Section: Mill Scale Referencesmentioning
confidence: 99%
“…However, mill scale containing oil must pass through treatment to remove this contaminant Bagatini et al (2011);El-Hussiny et al (2011);Martín et al (2012); Umadevi et al (2012) Manufacture of pigments It is possible to prepare various pigment shades based on iron oxide through a simple method (based on precipitation and calcination) and low cost Legodi and Dewaal (2007) Management routes of galvanic sludge.…”
Section: Mill Scale Referencesmentioning
confidence: 99%
“…It was also found that the reduction degradation index (RDI) and reducibility of the sinter decreased with the increasing mill scale addition which was attributed to the increase in FeO content, although there were no details of what proportion of FeO increase was produced in sintering compared to that already present in the raw materials. In their sinter pot investigation, El-Hussiny et al [12] similarly found that replacement of the initial iron ore concentrate with 5 wt pct mill scale increased the overall sinter strength, but the productivity decreased. These discrepant conclusions on the productivity change are likely caused by the difference in the physical form of the mill scale used.…”
Section: Introductionmentioning
confidence: 99%
“…Logo, a quantidade de carepa adicionada à mistura do sínter deve ser limitada, pois o sínter formado com excesso de carepa apresenta muitos finos em sua composição. Tem-se que a substituição de 5% de concentrado de minério de ferro por carepa na sinterização é a quantidade ideal para resultar em um aumento na força do sínter, além de elevar a produtividade tanto na sinterização quanto no alto-forno comparado ao material fabricado sem o resíduo [9].…”
Section: Fabricação De Sínterunclassified